PENGARUH LAJU AIR UMPAN DAN UDARA PADA GASIFIKASI FLUIDIZED BED LIMBAH KAYU KAMPER (DRYOBALANOPS SPP) - Tjutju Nurhayati; Hartoyo Hartoyo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
This research studied the fluizided bed gasification process of wood waste that could produce highly yield and good quality of fuel gas.The processing treatments were conducted at 3 levels of wood feed flow rate i.e 3. 6., 3.8 and 4.2 kgs/hour and 5 leveis of air flow rate i.e 4.4, 4.7, 5.0,5.4 and 6.5 m3/hour.The result revaled that highest caloriffic value of produced gas was 7.106 MJ/m3 which resulted from wood feed and air flow rate 3. 6 kg/hour and 4. 4 m3 /hour, respectively. The product gas composition of this rate was H2 = 5. 62 .CH = 3.99; CO= 11.77; C2H4 = 4.34; C2H6 = 0.21; N2 = 57.69; 02 = 0.40 and C02 = 15. 71 (in % volume)The highest total energy of product gas was 20.36 MJ/m3 with fuel gas efficiency 26.16% which resulted from feed and air flow rote 4.2 kg/hour and 6.5 m3/hour, respectively. The product gas composition at this rate was H2 = 6.03; CH4 = 3.51; CO= 12.60; C2H4 = 2.46; C2H6 = 0.16; N2 = 57.23; 02 = 0.45 and C02 = 17.58, while the fluidued bed gasification process was held at 97oᵒC.